Pengaruh Organizational Citizenship Behavior, Stres Kerja Dan Kepribadian Terhadap Kinerja Personel Dit Resnarkoba Polda Sultra - Hasnani Hasnani; Nurwati Nurwati; Wahyuniati Hamid; Alida Palilati; Nursaban Rommy Suleman; Yusuf Yusuf (Pascasarjana Universitas Halu Oleo, 2023)
This study aims to examine and analyze the effect of organizational citizenship behavior, work stress and personality on the performance of the North Sulawesi Regional Police Narcotics Directorate Personnel. This research is a quantitative approach. The population in this study is the Personnel of the Drugs and Drugs Directorate of the Southeast Sulawesi Regional Police with a sample of 60 people. The analysis used multiple regression analysis with the help of IBM SPSS 22 Software. The results showed that (1) Organizational citizenship behavior, work stress and personality together had a positive and significant effect on the performance of the North Sulawesi Regional Police Narcotics Directorate Personnel, (2) Organizational citizenship behavior had a positive and significant impact on the performance of the North Sulawesi Regional Police's Drug Directorate Personnel, (3) Work stress has a positive and insignificant effect on the performance of the North Sulawesi Regional Police's Drug Directorate Personnel and (4) Personality has a positive and significant impact on the performance of the Southeast Sulawesi Regional Police's Narcotics Directorate Personnel.